a APLIKASI LOGIKA FUZZY UNTUK MENENTUKAN BESARAN GAJI KARYAWAN MENGGUNAKAN METODE FUZZY MAMDANI BERBASIS WEB (STUDY KASUS : PT. KEMUNING PERSADA): APLIKASI LOGIKA FUZZY UNTUK MENENTUKAN BESARAN GAJI KARYAWAN MENGGUNAKAN METODE FUZZY MAMDANI BERBASIS WEB (STUDY KASUS : PT. KEMUNING PERSADA) - Runisati Waruwu Runi; romi andrianto (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2022)
PT. Kemuning Persada is a company engaged in finance. In determining the salary of PT. Kemuning Persada requires an application using the Fuzzy Mamdani method and making system designs according to needs that is run through modeling, making use case diagrams, sequence diagrams, class diagrams, user interface designs and then proceeding with coding according to the design made. Fuzzy Logic has three methods, namely, Sugeno, Tsukamoto and Mamdani of these three fuzzy methods have an inference and defuzzification engine. In the design, the Mamdani method is used. This research produces an application that can help employees of PT. Kemuning Persada in receiving salaries.